GEOCHEMISTRY AND COLOR OF NATURAL FLUORITES: EFFICIENCY AND SIMPLICITY OF PRACTICAL APPLICATION IN MINERALOGICAL AND GEOCHEMICAL STUDIES - Lazareva І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Research on fluorite indicator properties primarily focuses on the formation processes and geological setting of ore occurrences in order to predict fluorspar deposits. Recent papers have suggested new data on fluorite properties (REE distribution, isotopic ratios, color and luminescent properties and even morphology) indicative of mineralization. These properties differ in information value, which limits the range of their application. The objective of the paper was to assess the indicator properties of color and distribution for the most common trace elements in accessory fluorites (Sr, Y) in order to enhance the methodology of extensive mineralogical research. Our study focused on a large set of data on trace-element composition and the color of fluorite grains extracted from various Suschano-Perzhansk zone (SPZ) metasomatites and the Korosten pluton (KP) granitoids of the Ukrainian shield that have spatial association and show genetic affinity. The following tasks have been accomplished: (1) fluorite grain typing based on geochemical characteristics; (2) fluorite grain typing based on color; (3) geochemical modeling of the trace element composition of metasomatic fluorite aimed at confirming the results of the geochemical typing; (4) identifying fluorite-zircon paragenesis in different mineral types of metasomatites; (5) determining the Y relationship for the fluorite-zircon paragenetic pairs and their formation temperatures; (6) analyzing the information value of the fluorite geochemical properties and color. Our research yielded data on the geochemical types of fluorite suggesting the multiphase formation of the SPZ metasomatites. There was also identified the type of fluorite relating to the major metasomatic phase (by the trace element ratios and the age estimation). Results of geochemical typing were confirmed by geochemical modeling of the trace element composition of fluorites that are genetically related to the KP magmatogene-hydrothermal system. Geochemical modeling allowed us to suggest selection criteria for the fluorite-zircon paragenetic pairs; to determine linear dependence for the selected pairs ln Fl Zrn Y K – 1000 T ; to test the temperature dependence by solving the inverse equation. The minimally sufficient set of the constitutive elements of fluorite under study may be reduced to the most typical trace elements (Sr, Y) characterized by simplicity of analytical assessment and genetic information value which is potentially equal to that of REE. Observations on the selected groups of fluorite color features generally confirm the results of geochemical typing.